Coordinated control of active steering and active roll control systems for enhanced vehicle lateral dynamics. Issue 4 (2016) - Li, Bin; Fu, Zhi-Jun
In this paper, the coordinated control of active steering and active roll control systems is investigated aiming to enhance vehicle lateral dynamics performance. A combined control structure is employed to design active steering controller, in which feedback controller is designed using robust mixed sensitivity control approach to minimise the tracking error of yaw rate and body sideslip angle. To further improve vehicle cornering capacity, an active roll controller based on the yaw rate feedback is designed by re-distributing roll moments between the front and rear axles to collaborate together with active steering. The proposed control system is evaluated via computer simulations under different manoeuvres. The simulation results show the overall performance improvement using the proposed coordinated control system in terms of the better handling performances.